Symbiotic communities associated with nursery-reared and natural corals: are they similar? - Britayev, T. A.; Zvonareva, S. S.; Lishchenko, F. V.; Deart, Y. V. (Frontiers in Marine Science, 2023)
Coral aquaculture techniques have been developed for many species based on a well-documented understanding of the factors that affect coral growth and fitness. However, there is limited knowledge about the composition and structure of ectosymbiotic communities associated with cultured coral colonies. To address this gap, we conducted a study of Pocillopora verrucosa colonies reared from fragments in fixed nurseries and exposed for 6 and 12 months, as well as natural colonies in the same location. Our analysis focused on the species composition, species richness, and density of obligate and facultative ectosymbionts associated with the colonies. Obtained results indicate that the community associated with nursery-reared colonies was highly diverse, comprising 25 ectosymbionts, including 9 obligate and 16 facultative species. The prevalence, species richness, and density of the communities associated with natural colonies were significantly higher than those associated with reared ones. We also observed differences in the communities associated with reared colonies of different exposures, but we were able to group them as stages of the same community based on the size and exposure of the colonies. The differences between communities associated with reared and natural colonies may be related to the microhabitat properties of the symbiotic communities, as the former were elevated above the substrate, while the latter were attached to it. The age of natural colonies was also estimated to be more than three times higher than that of reared colonies of the same size, contributing to the differences. Our study clearly demonstrates that coral nurseries not only serve as a means of propagating corals but also offer artificial habitats for the maintenance and conservation of associated fauna. These findings have important implications for the management and conservation of coral reefs.